Natural fiber reinforced polymer composites - Saiful Islam, Md.; Kovalcik, Adriana; Hasan, Mahbub; Thakur, Vijay Kumar (Hindawi Publishing Corporation, 2015)
The use of natural fibers as a reinforcement for various materials was recorded already in ancient Egypt; however, their rediscovery can be dated to the beginning of 20th century. Currentspecial issueisdevoted to theroleofnatural fibersas reinforcements for various biodegradable and nonbiodegradable polymer matrices. The application of natural fillers can be seen as an approach to adjust material performance of polymer composites supposing that filler/matrix interactions will be optimized and a hygroscopicity of natural fillers will be hindered. This special issue contains 16 papers that highlight a number of reasons for applications of natural fillers in polymer composites. In recent years the discussion about a balance in carbon footprint increased an attractiveness of natural fibers/fillers derived from agricultural sources predominantly from one-year plants.